(untitled) (Research, Society and Development, 2021)
Various obstructive deformations of congenital etiology make up the brachycephalic syndrome, among them stenosis of the nostrils and prolongation of the soft palate. Early diagnosis and surgical treatment are of great importance, in order to minimize the disease progression and the imminent risk of death for the patient. This paper aims to report the use of diode laser in the surgical correction of stenosis of the nostrils and soft palate prolongation in a one-year-old brachycephalic dog with clinical symptoms of inspiratory dyspnea, snoring, exercise intolerance and syncope. The animal underwent rhinoplasty and palatoplasty with diode laser, and showed significant clinical improvement after the procedures, proving that the use of the diode laser is effective in the treatment of brachycephalic syndrome, bringing good functional and aesthetic results and improving well-being and quality of life of the animal.